Peculiarities of Rave Culture in Lithuania (on the "True" and the "Fake" Ravers) - Šliavaitė, Kristina (Sociologija. Mintis ir veiksmas, 1999)
The aims of this article is to discuss and interpret the internal hierarchical principles of Lithuanian rave subculture. The article is based on 11 conversations, acquired through an informal interviews with the representatives of Lithuanian rave culture. The interviews were held in January and February of 1998. The analysis of the interviews revealed certain stereotypes defined through binary distinctions: alternative-commercial, underground culture-mass media, center-periphery, male raver-female raver, and true raver-fake raver. The analysis is developed by discussing the role of stereotypic distinctions for the internal hierarchy of the subculture.
Keywords: raver; subculture; binary distinction; internal hierarchy of the subculture